2001
DOI: 10.1095/biolreprod65.1.79
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Hamster Sperm Protein P26h During Spermatogenesis1

Abstract: P26h is a hamster sperm protein of 26 kDa that has been previously characterized as a surface protein covering the acrosome acquired during epididymal transit. P26h is involved in sperm-egg interactions. Recently, it has been shown that the P26h transcript is highly expressed in the testis, and the P26h cDNA has been cloned from a hamster testicular cDNA library. Herein we report the production of a fusion protein (maltose binding protein-P26h) with the whole P26h cDNA encoding sequence and the production of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 29 publications
0
12
0
1
Order By: Relevance
“…They are known to encode highly abundant gene products of the human epididymis, or gene products enriched in specific regions that provide important functional clues [41]. These data complete the list of the two fundamental epididymal human genes, DCXR and NPC2, known to be affected by vasectomy [17,64].…”
Section: Discussionmentioning
confidence: 84%
“…They are known to encode highly abundant gene products of the human epididymis, or gene products enriched in specific regions that provide important functional clues [41]. These data complete the list of the two fundamental epididymal human genes, DCXR and NPC2, known to be affected by vasectomy [17,64].…”
Section: Discussionmentioning
confidence: 84%
“…In most cases, the disappearance of sperm surface proteins is caused by a specific proteolytic mechanism [10]. P26h, a member of the short-chain dehydrogenase/reductase superfamily, is not detected in caput epididymal hamster sperm, but appears on the acrosomal region in corpus epididymal sperm and accumulates on the acrosomal cap of cauda epididymal sperm [26]. Similarly, P25b is transferred to the sperm head during epididymal transit in the bull [27].…”
Section: Discussionmentioning
confidence: 99%
“…It was proposed that P26h is anchored to the membrane through a phosphaditylinositol linkage and that prostasome-like particles may be involved in the transfer of P26h from the epididymal fluid to the sperm plasma membrane [25]. Later, the same group of investigators cloned a cDNA from a hamster testicular cDNA library and reported that P26h is a member of the shortchain dehydrogenase/reductase superfamily [31]. They also found the predominant expression of P26h transcript in the seminiferous tubules of the testis, not the epididymis, and proposed that the epididymal luminal fluid P26h is secreted by the seminiferous tubules of the testis [31].…”
mentioning
confidence: 99%
“…Later, the same group of investigators cloned a cDNA from a hamster testicular cDNA library and reported that P26h is a member of the shortchain dehydrogenase/reductase superfamily [31]. They also found the predominant expression of P26h transcript in the seminiferous tubules of the testis, not the epididymis, and proposed that the epididymal luminal fluid P26h is secreted by the seminiferous tubules of the testis [31]. They also proposed that P26h may have two different functions, as observed for other moonlighting proteins [32]: first in the testis, as an alcohol dehydrogenase, and then in the epididymis, where it adsorbs on the sperm surface and plays a role during fertilization.…”
mentioning
confidence: 99%